The Oxford handbook of clinical geropsychology - Pachana, Nancy A.; Laidlaw, Ken (Oxford library of psychology, 2015)
This volume provides students and experienced clinicians and clinical researchers alike with a comprehensive and contemporary overview of developments in the field of geropsychology. Informed by an international perspective, the introductory section covers demographics, meta-analyses in geropsychology, social capital and gender, cognitive development, and ageing. Sections on assessment and formulation include chapters on interviewing older people, psychological assessment strategies, capacity and suicidal ideation, and understanding long term care environments.